Cytopathologic characteristics of the primary strumal carcinoid tumor of the ovary: A case report with emphasis on differential diagnostic considerations. Issue 9 (5th December 2011) - Hayashi, Toshitetsu; Haba, Reiji; Kushida, Yoshio; Kadota, Kyuichi; Katsuki, Naomi; Miyai, Yumi; Shibuya, Shinsuke; Sasaki, Makiko; Bando, Kenji; Matsunaga, Toru; Hata, Toshiyuki
<x xml:space="preserve">Abstract</x> Primary strumal carcinoid tumor of the ovary (SCTO) is an extremely rare entity, though the survival rate is excellent if the disease is confined to one ovary. A case is presented here in which intraoperative squash smears in a 45‐year‐old woman with a left adnexal mass revealed dispersed or small clusters of neoplastic cells forming loosely cohesive gland‐like structures with abundant cytoplasm. The nuclear chromatin was finely granular with a "salt and pepper" appearance and occasional tiny nucleoli. The position of the nucleus presented a vaguely plasmacytoid appearance. Small fragments of thyroidal colloid‐like structures were also identified. A cytopathologic diagnosis of a SCTO was suggested. Further evaluation and immunohistochemical studies were conducted on formalin‐fixed, paraffin‐embedded material. Cords or nests of uniform cells with abundant cytoplasm, and eccentric nuclei with coarse chromatin and occasional colloidal tissue were identified on H&E sections. The tumor cells showed diffuse and strong cytoplasmic staining for chromogranin A, synaptophysin, CD56, and vimentin but were negative for calretinin, α‐inhibin or CDX2. The proliferative index with MIB‐1 was around 3%. Thyroidal colloid‐like structures were immunoreactive for thyroglobulin and TTF‐1 stains. The diagnosis of primary SCTO was confirmed based on cytopathologic, histopathological, and immunohistochemical results, and the location of the tumor. Awareness of the cytopathological findings of SCTO can assist in diagnosing this rare entity correctly. Diagn. Cytopathol. 2013;41:812–816. © 2011 Wiley Periodicals, Inc.